Policies for competitive and sustainable agricultural production systems: A case study of Ghana’s recent mechanization interventions - Takeshima, Hiroyuki; Diao, Xinshen; Aboagye, Patrick Ohene (International Food Policy Research Institute, 2020)
This chapter highlights the emerging areas of market failure associated with agricultural mechanization and how SSA governments, including the Ghanaian government, have adapted their strategies over the years in attempting to overcome these market failures. The chapter focuses more on Ghana, rather than SSA as a whole, while also discussing how Ghana’s experiences are still relevant to other SSA countries. To retain clarity on the policy dynamics aspects, the chapter limits its focus to tractors in the crop subsector, as well as mechanization-specific policies, while leaving other types of mechanization technologies or subsectors, or other broader mechanization-sensitive interventions and policies, to future studies.